Faulty Predictions - Lin-Greenberg, Karin (Book collections on Project MUSE., 2014)
"In Karin Lin-Greenberg's Faulty Predictions, young characters try to find their way in the world and older characters confront regrets. In "Editorial Decisions," members of the editorial board of a high school literary magazine are witnesses to an unspeakable act of violence. Two grandmothers, both immigrants from China, argue over the value of their treasures at a filming of Antiques Roadshow in "Prized Possessions." In "A Good Brother," asister forces her brother to accompany her to the Running of the Brides at Filene's Basement. A city bus driver adopts a pig that has been brought onto the bus by rowdy college students in "Designated Driver." The stories in Faulty Predictions take place in locales as diverse as small-town Ohio, the mountains of western North Carolina, and the plains of Kansas. Lin-Greenberg provides insight into the human condition over a variedcross section of geography, age, and culture. Although the characters are often faced with obstacles and challenges, the stories also capture moments of optimism and hope."--